2011
DOI: 10.1038/ajg.2010.490
|View full text |Cite
|
Sign up to set email alerts
|

Can Gluten Contribute to Irritable Bowel Syndrome?

Abstract: Functional gastrointestinal disorders are the most common gastroenterological problem in our society. Changes in gut function, including pain perception, motility, and intestinal permeability, and low-grade infl ammation have been described in patients with irritable bowel syndrome (IBS). The triggering factors for the described immunity and gut functional changes in patients with IBS are not completely understood. Similarly to post-infective IBS, some patients with IBS symptoms exhibit immunological evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
0
17
0
2
Order By: Relevance
“…The definition is necessarily broad, as many clinical manifestations are attributed to gluten sensitivity, ranging from strictly gastrointestinal to extra-intestinal such as fatigue, headaches, joint pain. Gastrointestinal manifestations however appear to be the most common complaint of affected individuals, to the point that looking for gluten sensitivity (in addition to celiac disease [39]) has been recommended in patients with irritable bowel syndrome [40]. Two very recent studies [41,42] showed the glutendependency of symptoms in such patients, and also supported the notion that so far, no clear-cut biological markers useful for diagnosis are available.…”
Section: Possibly Immune-mediatedmentioning
confidence: 91%
“…The definition is necessarily broad, as many clinical manifestations are attributed to gluten sensitivity, ranging from strictly gastrointestinal to extra-intestinal such as fatigue, headaches, joint pain. Gastrointestinal manifestations however appear to be the most common complaint of affected individuals, to the point that looking for gluten sensitivity (in addition to celiac disease [39]) has been recommended in patients with irritable bowel syndrome [40]. Two very recent studies [41,42] showed the glutendependency of symptoms in such patients, and also supported the notion that so far, no clear-cut biological markers useful for diagnosis are available.…”
Section: Possibly Immune-mediatedmentioning
confidence: 91%
“…NCGS may be involved in the pathogenesis of a subgroup of irritable bowel syndrome patients, but we lack knowledge which gluten, if any, can contribute to functional bowel disorders [21]. NCGS has yet, by any means, to explain all intolerance to food.…”
Section: Resultsmentioning
confidence: 99%
“…We can hypothesize that the inner ear, like other extraintestinal sites involved in GS, could become the target of an immune mediated response. Likewise, a subclinical sensorineural hearing loss, affecting mainly the high frequencies, has been associated with irritable bowel syndrome 17 , a syndrome in which GS has been suggested as a possible pathogenic factor 18 . Tinnitus is a symptom of multifactorial origin.…”
Section: Discussionmentioning
confidence: 99%